A 5-Year-Old Child with a Deep Neck Abscess Complicated by Laryngeal Obstruction - Armando Di Ludovico; Massimiliano Raso; Paola Di Filippo; Sabrina Di Pillo; Roberta Zappacosta; Giustino Parruti; Pasquale Zingariello; Francesco Chiarelli; Marina Attanasi (MDPI AG, 2022)
Deep neck space infections (DNSI) are defined as infections in the potential spaces and fascial planes of the neck. We show the clinical case of a retro and para-pharyngeal abscess in a healthy 5-year-old child complicated by compression and dislocation of the larynx with marked airway caliber reduction and potentially fatal extension up to the mediastinal aditus. DNSI can occur at any age and, due to its rapid progression, requires immediate treatment in children. In healthy children, concurrent abscesses in separate neck spaces are rare. DNSI recurrence should alert the physician to the possibility of a congenital problem, and if imaging fails, laryngoscopy may be the best diagnostic technique.